Obtaining gas dynamic characteristics of the circulation centrifugal compressor of hydrogen-containing gas based on the analysis of actual operating modes - A. D. Vanyashov; D. V. Bychkov; A. V. Belikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2025)
The analysis of actual operating modes of a centrifugal compressor providing circulation of hydrogencontaining gas in a reactor block of catalytic isomerization of metaxylene and ethylbenzene into orthoxylenes and paraxylenes has been performed. The technological process, as well as the state and properties of the catalyst in the reactor block determine the concentration of hydrogen and the molecular weight of the gas mixture, which, accordingly, leads to the need to regulate the operating modes of the centrifugal compressor by throttling at the suction. The calculation method of the gas-dynamic characteristics of the compressor when regulating by throttling at the suction has been clarified, taking into account the features of operation in the circulation mode, namely, the change in pressure before the throttling device. It has been established that when regulating by throttling at the suction of a circulation centrifugal compressor, the function of the pressure ratio on the volumetric productivity changes. It is established that the actual surge limit is shifted relative to the theoretical limit to the left, into the zone of the descending part of the pressure characteristic.